The first Peary collection of polar Eskimo material culture / Fieldiana, Anthropology, v. 63, no.2 - VanStone, James W. ([Chicago] Field Museum of Natural History, 1972)
Includes bibliographical references (p. 72-73). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).